Nutritional requirements and nitrogen-dependent regulation of proteinase activity of Lactobacillus helveticus CRL 1062 - Hebert, Elvira Maria (2000)
The nutritional requirements of Lactobacillus helveticus CRL 1062 were determined with a simplified chemically defined medium (SCDM) and compared with those of L. helveticus CRL 974 (ATCC 15009). Both strains were found to be prototrophic for alanine, glycine, asparagine, glutamine, and cysteine. In addition, CRL 1062 also showed prototrophy for lysine and serine. The microorganisms also required riboflavin, calcium pantothenate, pyridoxal, nicotinic acid, and uracil for growth in liquid SCDM. The growth rate and the synthesis of their cell membrane-bound serine proteinases, but not of their intracellular leucyl-aminopeptidases, were influenced by the peptide content of the medium. The highest proteinase levels were found during cell growth in basal SCDM, while the synthesis of this enzyme was inhibited in SCDM supplemented with Casitone, Casamino Acids, or β-casein. Low-molecular-mass peptides (<3,000 Da), extracted from Casitone, and the dipeptide leucylproline (final concentration, 5 mM) play important roles in the medium-dependent regulation of proteinase activity. The addition of the dipeptide leucylproline (5 mM) to SCDM reduced proteinase activity by 25%.